Molecular-beam epitaxy of monolayer MoSe2: growth characteristics and domain boundary formation. (15th May 2015) - Jiao, L; Liu, H J; Chen, J L; Yi, Y; Chen, W G; Cai, Y; Wang, J N; Dai, X Q; Wang, N; Ho, W K; Xie, M H
Abstract: Monolayer (ML) transition metal dichalcogenides (TMDs) are of great research interest due to their potential use in ultrathin electronic and optoelectronic applications. They show promise in new concept devices in spintronics and valleytronics. Here we present a growth study by molecular-beam epitaxy of ML and sub-ML MoSe2, an important member of TMDs, revealing its unique growth characteristics as well as the formation processes of domain boundary (DB) defects. A dramatic effect of growth temperature and post-growth annealing on DB formation is uncovered.